PENGARUH HEDONIC MOTIVATION, SOCIAL INFLUENCE, DAN PERCEIVED ENJOYMENT TERHADAP PENGGUNAAN MARKETPLACE PADA UMKM DI BALI: STUDI KASUS PADA HIPMI PROVINSI BALI - Permana, Gusi Putu Lestara; Parasari, A.A. Ayu Indah (Universitas Pendidikan Nasional, 2019)
The purpose of this research is 1) To find out the positive influence of Hedonic Motivation on the Use of Marketplace in UMKM registered in the Hipmi Province of Bali. 2) To find out the positive influence of social influence on the use of the marketplace in UMKM registered in the Hipmi Province of Bali. 3) To find out the positive influence of Perceived Enjoyment on the Use of Marketplace in UMKM registered in Hipmi Province of Bali. The technique of collecting data using a questionnaire. The sample in this study were 100 people who belonged to the active member of Hipmi Bali Province with a purposive sampling method. Data were analyzed using regression analysis techniques, descriptive statistics, determination, F test, and t test with the help of SPSS for Windows software. The results of the study found that 1) Hedonic Motivation had a positive and significant effect on marketplace use in UMKM. 2) Social Influence has a positive and significant effect on marketplace use in UMKM. 3) Perceived Enjoyment has a positive and significant effect on marketplace use in UMKM.Keywords: hedonic motivation, social influence, perceived enjoyment, umkm, marketplace